2020
DOI: 10.4314/tjpr.v19i4.4
|View full text |Cite
|
Sign up to set email alerts
|

Engelharquinone suppresses lipopolysaccharide-induced inflammation and proliferation of human liver cancer SMCC7721 cells via inhibition of NF-κB and MAPK signaling pathway

Abstract: Purpose: To investigate the anti-tumor effect of engelharquinone (Eng) on human liver cancer SMCC7721 cells.Methods: GFP-labeled SMCC7721 cells were used to establish a tumor-bearing mice model used for determination of the effect of different  concentrations of Eng on tumor growth. The effect of Eng on SMCC7721 cell viability was determined with MTT assay and cell cycle analysis. The anti-inflammatory effect of Eng on lipopolysaccharide (LPS)-treated SMCC7721 cells were determined through assay of pro-inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…138 possesses moderate antitubercular activity against Mycobacterium tuberculosis 90–221387. A recent report showed that 138 also inhibited LPS‐induced inflammation and proliferation of human liver cancer SMCC7721 cells via a mechanism involving the regulation of NF‐κB and MAPK signaling pathways [44b] . While isolated 138 and 139 were optically active, an enantioselective total synthesis from Ohmori and Suzuki group suggests that both may naturally occur in a scalemic form [46]…”
Section: Dibenzo[23 : 67]bicyclo[321]octanementioning
confidence: 99%
“…138 possesses moderate antitubercular activity against Mycobacterium tuberculosis 90–221387. A recent report showed that 138 also inhibited LPS‐induced inflammation and proliferation of human liver cancer SMCC7721 cells via a mechanism involving the regulation of NF‐κB and MAPK signaling pathways [44b] . While isolated 138 and 139 were optically active, an enantioselective total synthesis from Ohmori and Suzuki group suggests that both may naturally occur in a scalemic form [46]…”
Section: Dibenzo[23 : 67]bicyclo[321]octanementioning
confidence: 99%